Romantic oedipus from literature to cinema - Calaça, Fausto (2014)
In this present paper, we develop a compared analysis between the novel by Honoré de Balzac, Le Lys dans la vallée  (1836) and the movie by François Truffaut, Baisers volés (1968), having as perspective the following themes: disenchantment, nostalgia, learning romance, Nouvelle vague and the theme “Romantic Oedipus”, elaborated by Pierre Laforgue (2002). The drama of Antoine Doinel, the movie protagonist, is highlighted, which re-presents a similar episode to the trajectory of the young protagonist Félix de Vandenesse, from the novel by Balzac.